Theoretical Vibrational Mode Analysis of Schiff Bases using Semi Empirical Methods-II - Agnihotri, Sonal; Singh, Bhoop; Burman, Kiran; Arora*, Kishor (Asian Journal of Chemistry, 2011)
Two new Schiff bases viz., 2N-[(4-chlorobenzalidene)aminopyridine] and 2N-[(4-hydroxybenzalidene)aminopyridine] were synthesized using 4-chlorobenzaldehyde, 4-hydroxybenzaldehyde and 2-amino pyridine in separate procedures. Their IR spectra was obtained experimentally by KBr method and was analyzed for significant peaks. Semi empirical methods AM1, PM3, MNDO, ZINDO methods were used to compare the experimentally obtained IR spectra with the computer simulated IR spectra using transmittance vs. frequency plots given by four methods used here. Apart from the comparison of the significant part of the spectra, the statistical correlation was also calculated for the theoretical spectra and methods, to establish the use of these methods as alternative and supportive tool in analytical chemistry as well as to establish purity of the synthesized compound.